The Role of Different Monocyte Subsets in Progression of Coronary Atherosclerotic Lesion - Hamideh Rahimi; Mohammad Mehdi Peyghambari; Saeid Taghiloo; Hossein Asgarian-Omran; Reza Alizadeh-Navaei; Ali Heydari; Fatemeh Gabeleh; Abolghasem Ajami (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Circulating monocytes are divided into different subpopulations according to the expression of CD14 and CD16. In this study, we investigated the correlation between the severity of coronary artery disease (CAD) and the frequency of two monocyte subsets and also expression level of CCR1 receptor on these monocytes. Materials and methods: The study was conducted in 88 patients who underwent diagnostic coronary angiography (CAG) in Tehran Shahid Rajaee Heart Center, 2014-2015. The participants were selected using convenience sampling. They were divided into four groups: 50% stenosis in one vessel (MVD), single vessel stenosis (1VD), 2 or 3 vessels stenosis (2+3 VD), and no CAD as the control group. The severity of CAD was evaluated by Gensini score. Frequency of the two monocyte subsets, including classical (CD14+CD16-) and non-classical (CD14+CD16+) were measured by flow cytometry. Mean fluorescence intensity (MFI) of CCR1 receptor on monocyts was also measured in two subsets and all groups of patients. Results: Circulating non-classical monocytes were observed more frequently in patients with 2+3 VD than in controls, MVD, and 1VD groups, but the differences were not statistically significant (P> 0.05). Both classical and non-classical monocytes expressed CCR1, but it was expressed on higher number of classical monocytes than in non-classical ones. Also, no significant differences were seen in MFI of CCR1 in different groups. Conclusion: This study showed that higher frequency of non-classical monocytes was correlated with severity of CAD.